Performance of AlGaInP LEDs on silicon substrates through low threading dislocation density (TDD) germanium buffer layer - Wang, Yue (2020)
Performance of GaInP/AlGaInP multi-quantum wells light-emitting diodes (LEDs) grown on low threading dislocation density (TDD) Germanium-on-Silicon (Ge/Si) substrates are compared and studied. Three approaches are used to realize the low TDD Ge/Si substrates. The first approach is the two-step growth of Ge/Si substrate with TDD of ∼5 ×107 cm-2. The second approach is through doped the Ge seed layer with arsenic (As) and TDD of <5 ×106 cm-2 can be achieved. The third approach is through wafer bonding and layer transfer techniques, germanium-on-insulator (GOI) substrate with TDD of ∼1.2 ×106 cm-2 can be fabricated. To demonstrate the quality of these Ge/Si substrates, LEDs fabricated on commercially available Ge/Si and bulk Ge substrates were also included for comparison purposes. The LEDs fabricated on the As-doped Ge/Si and GOI substrates exhibit superior performances, with output light intensity at least 2× higher compared to devices fabricated on commercially available Ge/Si substrate. These findings enable the monolithic integration of visible-band optical sources with Si-based control circuitry.